Factores de riesgos y su influencia en la neumonía en adultos de 40 a 60 años en la ciudadela nueva Jerusalén, Babahoyo Los Ríos, durante el primer semestre del 2018. - Castro Vera, Eliel Emanuel (2018)
Pneumonia is the infectious disease that usually appears, especially during the cold months. A pneumoniae is a lung infection caused by a pathogen, the risk of pneumonia is especially high in those whose immune system is weakened, in the elderly and in young children. A cross-sectional study was conducted in order to determine the risk factors that influence the origin of pneumonia in adults aged 40 to 60 years in the ciudadela Nueva Jerusalén, Babahoyo Los Ríos during the first semester of 2018. The total of 78 adult patients aged 40 to 60 years who were treated at the health center on 4 de Mayo of the ciudadela with some respiratory pathology were considered both in the population and in the sample; With the information obtained from both the survey and the interview and from the review of the H. clinics, an excellent database was developed; As a result we have that overcrowding showed a percentage of 40%, smoking 42% and alcoholism with 29% and being the highest percentages within the risk factors gives a direct route to the origin of pneumonia